The Use of Picture Series of Central Kalimantan Folklore as a Visual Media in Teaching Writing of Narative Text - Girsang, Novita Desriana Br (Pusat Kajian Bahasa Daerah & Budaya, 2024)
The objective of this research was to determine whether the use of picture series could improve the generic structure of students' writing, specifically their ability to write narrative texts with proper generic structure. The researcher employed a pre-experimental design with a one-group pre-test and post-test format. The population consisted of ninth-grade students from SMP Negeri 14 Palangka Raya during the 2023/2024 academic year, comprising three classes. The sample size was 30 students from class IX-A. The research findings indicated that using picture series improved students' writing abilities in terms of generic structure, particularly in writing narrative texts. This was evidenced by the increase in students’ mean scores from 60.9 in the pre-test to 81.8 in the post-test, reflecting 20.9 points of improvement. After calculating the difference between the matched pairs, the t-test value was found to be 9.390. With a significance level (p) = 0.05 and a degree of freedom (df) = 29, the t-table value was 1.699. Since the t-test value was greater than the t-table value (9.390 > 1.699), the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted.